PENGARUH CURRENT RATIO, DEBT TO ASSET, DEBT TO EQUITY, RETURN ON ASSETS DAN PRICE EARNINGS RATIO TERHADAP HARGA SAHAM - NOFA PRILIYASTUTI; STELLA STELLA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to test and analyze empirically the influence of current ratio, debt to asset ratio, debt to equity ratio, return on assets, and price earning ratio toward stock price. The object of this research is wholesale and Retail trade companies that listed in Indonesia Stock Exchange period 2011 – 2015. The purposive sampling is used as sampling technique, where 12 companies met the criteria. The result of this research shows that current ratio and price earning ratio influence stock price, while debt to asset ratio, debt to equity ratio, and return on assets do not influence stock price.